Quasi-optical characterization and preliminary experimental results of electron cyclotron emission imaging on HL-3 tokamak - HAN, Kexi; SHI, Zhongbing; YU, Xin; JIANG, Min; YANG, Zengchen; ZHOU, Yu; SHEN, Yuqi; DENG, Weichu; HU, Liwen; LIANG, Anshu; SHI, Peiwan; XU, Sen (Plasma science & technology, 2025)
Electron cyclotron emission imaging (ECEI) is a critical diagnostic tool for measuring two-dimensional electron temperature fluctuations. The optical system, a key component of the ECEI diagnostic, determines the spatial resolution, field of view, and imaging performance of electron temperature fluctuations. In this study, comprehensive laboratory tests and characterizations of the optical system, including the local oscillator (LO) coupling optics and the radio frequency (RF) receiving optics, were conducted to ensure optimal performance during plasma discharge experiments. Laboratory testing of the LO optics revealed that the light intensity at the edge channels reaches 36% of that at the central channels; however, both are sufficient to effectively drive the down-converted mixers. The RF optics focus covers the entire non-harmonic overlap region, corresponding to a normalized plasma minor radius range of ρ = −0.2 to 0.9, and offers three zoom modes: narrow, medium, and wide, with poloidal resolutions of 1.5 cm, 1.8 cm, and 2.1 cm, respectively. The characterizations for these zoom modes align well with the optical design specifications. It was observed that the imaging surfaces of all zoom modes are exceptionally flat, indicating high-quality ECEI measurements with excellent spatial resolution. The LO lens, focusing lens, and zoom adjustment lens are capable of remote independent control, which enhances the operational flexibility of the system. Preliminary analyses conducted with the ECEI system successfully captured the two-dimensional structure and spatiotemporal evolution of phenomena such as sawtooth crashes, demonstrating the robust capability of the system to provide valuable insights into plasma dynamics.